THE DIFFICULITIES IN SPEAKING ENGLISH ON FIRST GRADE STUDENTS’ AT SMAN 4 KOTA SERANG - Rita Handayani; Tita Irawati; Rayna S. Zahara; Altasya, Ajeng (Aisyah Journal of English Language Teaching (AIJELT), 2023)
It is undeniable that learning to speak is an important skill in the English language. It is a fact that Indonesian students find it challenging to speak English. Both linguistic and non-linguistic factors may be to blame. Finding out why students have trouble speaking English and the reasons behind those difficulties were the goals of the study. A descriptive qualitative method research design was used. Students in SMAN 4 Kota Serang’s tenth grade served as the study’s subjects. The study results present that the tenth-grade students at SMAN 4 Kota Serang were having obstacles in speaking English. Three language-related issues were found when speaking English: poor pronunciation, insufficient vocabulary, and poor of grammar. The personal problems of the students involved two challenges; nervousness and lack of confidence. The reason why students struggled with speaking English was that they were fear of making a mistake.